2008
DOI: 10.1093/jmedent/45.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Distribution and Abundance of West Nile and Eastern Equine Encephalomyelitis Virus Vectors in Suffolk County, New York, Using Human Population Density and Land Use/Cover Data

Abstract: Five years of CDC light trap data from Suffolk County, NY, were analyzed to compare the applicability of human population density (HPD) and land use/cover (LUC) classification systems to describe mosquito abundance and to determine whether certain mosquito species of medical importance tend to be more common in urban (defined by HPD) or residential (defined by LUC) areas. Eleven study sites were categorized as urban or rural using U.S. Census Bureau data and by LUC types using geographic information systems (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…tarsalis in Western regions. 5,6,10,11,[31][32][33][34][35][36][37][38] Supplemental Figure S2 has a range map of these species. 24 A few studies have reported results that were contradictory to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…tarsalis in Western regions. 5,6,10,11,[31][32][33][34][35][36][37][38] Supplemental Figure S2 has a range map of these species. 24 A few studies have reported results that were contradictory to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Land cover/ vegetation indices (Moncayo et al 2000, DiukWasser et al 2006, Rochlin et al 2008, canopy cover (Moncayo et al 2000), soil properties (Patz 1998), elevation , Jacob et al 2010, and hydrology (Shaman et al 2002), are just a few of the known environmental variables which have been shown to be associated with the local abundance of a particular mosquito species. Diuk-Wasser et al (2006) demonstrated the predictive capabilities of GIS for mosquitoes by using remotely sensed landscape elements to model relative abundances of arbovirus vectors, then testing the validity of their models using trapping data from 31 sites, over a three-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of many disease risk models depends on the relationship between habitat features and vector abundance (Brownstein et al 2002, Diuk-Wasser et al 2006, Peterson et al 2008, Rochlin et al 2008. However, one of the most important pathways by which humans alter natural habitats is by the introduction of nonnative species into novel landscapes (Hobbs and Humphries 1995), and the distribution of many invasive species is linked to human disturbance and human population centers (Bartuszevige et al 2006, Thuiller et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The geographic range of A. triseriatus encompasses most of the eastern United States, from Maine to Montana in the north to Florida and Texas in the south (Jenkins and Carpenter 1946). Understanding the habitat preferences of A. triseriatus is important for assessing disease risk because, as a container-breeding mosquito that utilizes both abandoned tires as well as natural phytotelmata, it is frequently associated with habitats in close proximity to human habitation (Rochlin et al 2008). Although such areas of high oviposition activity do not necessarily correlate directly with areas of high adult density (Ellis 2008), they remain important for understanding vector distribution because models of disease risk report strong correlations between distances from breeding habitat, biting intensity, and rates of disease transmission (Beaty and Thompson 1975, Smith et al 2004, Le Menach et al 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation